Seasonal prevalence of extended-spectrum β-lactamase–producing bacteria in food-chain animals, humans, and the surrounding environment in Fayoum governorate: a one health approach - El-Zayat, Ayatollah S.; Khalil, Shrouk E.; Ahmed, Marwa N.; El-Sayed, Dina; Rabie, Neveen; Farag, Enas A. H.; Goda, Hanan A.; Al-Shahaby, Ahmad F.; Ali, Hala R. (Frontiers in Microbiology, 2026)
Extended-spectrum β-lactamase (ESBL) producers, particularly Escherichia coli and Klebsiella pneumoniae, pose a growing One Health challenge influenced by seasonal variation. This study assessed seasonal impacts on ESBL prevalence among humans, animals, and farm environments. A total of 2,890 poultry samples, 864 samples from dairy cows (including 88 milk samples and 776 rectal swabs), 248 human fecal samples (118 farm workers and 130 hospitalized patients) and 583 environmental samples were collected from Fayoum governorate, across three seasons. The isolation data revealed significant seasonal impacts, particularly in dairy cows and environmental samples, with source-related differences evident within the same season. The phenotypic and genotypic ESBL- analysis of all isolates from different sources across seasons showed that ESBL-producing E. coli demonstrated comparable prevalence in summer (14.68%) and fall (15%) before declining in winter (7.5%), while K. pneumoniae showed the highest prevalence in winter (29.4%), with lower detection in summer (11.9%) and absence in fall. Significant seasonal differences were detected, with ESBL-producing E. coli prevalence varying across sources in the fall (p = 0.039) and ESBL-producing K. pneumoniae showing variation in poultry across seasons (p = 0.042). Environmental isolates exhibited fluctuating trends, highlighting the role of farm environments in ESBL persistence and dissemination. At the genetic level, blaSHV and blaCTX-M1 demonstrated seasonal variation, whereas blaTEM showed no variation. Heat-map and hierarchical clustering showed significant correlation among harboring ESBL-genes, particularly blaSHV and blaCTX-M1, and resistance profiles to β-lactams antibiotics, as well as to non-beta-lactam antibiotics. Additionally, source- and species-based seasonal effects were observed in the prevalence of E. coli, K. pneumoniae, and their associated ESBL traits. The results further demonstrated that genotypic resistance determinants (bla genes) are significantly linked to phenotypic resistance, especially to β-lactams, and also reflected multi-drug resistance patterns that indicate co-selection across unrelated antibiotic classes. These findings highlight the public health significance of ESBL-producing E. coli and K. pneumoniae, both as pathogens and as disseminators of multidrug resistance determinants, emphasizing the need for One Health surveillance. To the best of our knowledge, this is the first systematic and comprehensive investigation of ESBL prevalence across animal, human and environmental, over three distinct seasons.